Diagnostic value of Anti-CCP antibodies compared with Rheumatoid factor in Rheumatoid arthritis patients. - Hanaa N. Abdullah; Amina N.Al-Thuwani; Mohamed I. Nadi; Khudhair Al-Badri (مجلة جامعة الانبار للعلوم الصرفة, 2013)
Citrullinated proteins have been discovered in the joints of patients with rheumatoid arthritis but not in other forms of joint disease. The citrullinated proteins in the joints correspond to the presence of the citrulline antibodies in the blood and suggest a possible role for these antibodies in the development of rheumatoid arthritis. The present study assessed the recent diagnostic value of anti-cyclic citrullinated antibodies (CCP) compared with rheumatoid factor (RF) in patients with rheumatoid arthritis. One hundred blood samples were collected from RA patients and thirty from apparently healthy group. Sera from each subject were tested for anti- CCP and RF by enzyme linked immunosorbent assay (ELISA). The majority of patients were females (84%), with a female: male ratio 5.2:1. The results indicated that anti-CCP postivity for RA patients was (69%) when compared with the healthy group (0.0%), which was highly significant in RA in comparison with control groups (P<0.001). The current study revealed that the sensitivity and specificity of Anti-CCP appeared the highest (69%) in comparison with low (47%) sensitivity for RF. Moreover, the specificity of Anti-CCP was very high (100%), while the specificity of RF was high (90%).